Key health information systems outsourcing issues from six hospital cases - Lin, C.; Huang, Y.; Li, C.; Jalleh, Geoffrey (2013)
© 2013 by IGI Global. All rights reserved. Traditionally, little attention has been paid by hospitals to the key issues in the health information systems (HIS) outsourcing decision-making process. This is important given that the HIS outsourcing can play a key role in assisting hospitals in achieving its business objectives. However, the decision-making process of HIS outsourcing in hospitals is under-studied, especially in the management of their HIS outsourcing contracts. Therefore, the main objectives of this book chapter are to: (1) examine key issues surrounding the management and implementation of HIS outsourcing in Taiwanese hospitals; and (2) identify issues that are crucial in managing and implementing HIS outsourcing in hospitals. Four key issues and problems were identified in the HIS outsourcing process: lack of implementation in IS investment evaluation process, problems in managing HIS outsourcing contracts, lack of user involvement and participation in HIS outsourcing process, and failure to retain critical HIS contract management skills and project management capabilities in-house. Solutions and recommendations are provided to deal with key issues that are critical in the management and implementation of HIS outsourcing in hospitals.